Full Informed Digital Transformation - Simpler, Maybe Better - Dias, Almeida (2021)
The digital age is upon us and challenges many of today’s businesses. To succeed with digitalization, it is needed a well-integrated enterprise and Information Technology organization that works seamlessly and thrives towards common goals. This is easy to say, but harder to achieve. Digital Transformation is the integration of digital technology into all areas of a business, fundamentally changing how one operates and delivers value to customers. It is also a cultural change that requires organizations to continually challenge the status quo, experimenting and coming to terms with doing something rather than making it perfect. This will be the focus of this work, which will be delivered as a computational agency integrating the phases of data gathering, the anticipation of a logic representation of uncertainty and vagueness, as well as the phases of data processing and analysis of results.